Inisiasi Kultur Tunas Melon IPB M23 In Vitro menggunakan Dua Jenis Eksplan dengan Kombinasi IAA dan BAP: In Vitro Shoot Cultures Initiation of IPB M23 Melon by Using Two Types of Explants with Combination of IAA and BAP - Sukma, Dewi; Syilvia Nosya Pratama; Willy Bayuardi Suwarno (Jurnal Hortikultura Indonesia, 2022)
In vitro propagation of melon seedlings produces pathogen-free, uniform, true to type seeds that can be obtained in large quantities quickly. This study aims to determine the optimal combination of IAA and BAP for the initiation of melon shoot culture in vitro. This study was carried out in January-July 2018, using a three-factor randomized complete group design with 6 replicates. The first factor is three IAA levels, namely 0.0, 0.25, and 0.5 ppm. The second factor is the four levels of BAP, namely 0.0, 1.0, 1.5, and 2.0 ppm, and the third factor is the type of explant, namely shoots and cotyledon nodes. Single factors (IAA, BAP, explant type) had a significant effect on the number of shoots and leaves, the interaction of two or 3 factors had no significant effect on the number of shoots and leaves, except that the interaction of IAA and BAP had a significant effect on the number of roots. Apical shoot explants produce more shoots than cotyledon nodes. The results of regression analysis showed that the influence of BAP tended to form a positive quadratic pattern on the variables of the number of shoots and the number of leaves, but it was linearly negative with the variable of the number of roots. The optimal medium for shoot multiplication is the medium containing BAP 1.0 ppm. Higher concentrations of IAA and BAP induce callus formation and suppress shoots growth.Keywords: apical shoot, auxin, cytokinin, seedling, single node